Tipologi Nalar Fiqh Wakaf dalam Baḥth al-Masâil NU - Nawawi Nawawi (Islamica: Jurnal Studi Keislaman, 2013)
Many argued that the NU discourse concerning the idea of endowment is rather static and textual. This can be seen particularly from the so-called Baḥth al-Masâil, the discussion forum being held regularly by the NU to address various legal issues faced by the community. The forum often comes to no veil. Since 1998 however, the younger generation of the NU initiated the idea of reading the classical thought in contextual terms. This paper addresses this issue by mapping out the typology of NU thinking particularly regarding the notion of endowment. This typology is drawn up from the Baḥth al-Masâil being held from 1926-2006, and found that there are at least four types of thinking within the organization. First, the restrictivetextual thinking, which looks at the issue of endowment by referring to the Shafiite classical works; second, the electivetextual thinking, which tends to select the most preferable view on a particular issue of endowment; and third, progressive-contextual thinking, which tends to employ the method of collective ijtihâd. The paper discusses these three variants by explaining their characteristics and development.